Determinants of Smallholder Farmers’ Income Diversification in Sodo Zuria District, Southern Ethiopia - Atalelech W/kidan; Alula Tafesse (Advances in Agriculture)
The research aimed to estimate income diversification and investigate demographic, socioeconomic, and institutional factors that determine the smallholder farmer’s diversification of income in the Sodo Zuria district, southern Ethiopia. Cross-sectional data were collected from 353 randomly selected households. The Simpson Index of Diversity was used to summarize income diversification, and the Tobit econometric model was implemented to explore the factors affecting the income diversification of smallholder farmers. Accordingly, the mean earnings diversification among smallholder farmers was estimated at 0.56. The primary household income sources are livestock rearing, crop production, mixed farming, nonlabor income, agricultural wages, and nonagricultural wage employment. We found household age, family size, livestock ownership, use of agricultural inputs, access to credit, and participation in training activities significant factors determining smallholder farmers’ income diversification in the research area. Lack of initial capital and market access were the principal challenges to diversifying income sources. Therefore, decision-makers should work on the indicated predictors to improve income diversification activities in the study area; particularly, it is required to focus on effective credit provision systems by using modern technologies, improving agricultural input supply, and equipping farmers with better knowledge and skills on income diversification through short-term training.